The Influence of Product Quality, Price and Location against The Satisfaction and The Image of The Impact on Consumer Loyalty (Empirical Study in Waroeng Special Sambal Sragen Branch) - Sunarmo, Sunarmo (STIE AUB Surakarta)
This study aims to identify and analyze the effect of product quality, price and location of the satisfaction and the image of the impact on consumer loyalty Waroeng Special Sambal Sragen Branch. This research is quantitative research using questionnaires or questionnaire as the primary data that is processed in SPSS program. The analysis technique used is using validity and reliability test, linearity test, regression analysis, path analysis, t test, F test, test the coefficient of determination and correlation analysis. The results showed that the quality of products significantly influence customer satisfaction. Price significant effect on customer satisfaction. The location is not significant effect on customer satisfaction. Product quality significantly influence the image. Price significant effect on consumer image. Locations significant effect on the image. Product quality significantly influence consumer loyalty. Price significant effect on loyalty. Locations significant effect on loyalty. Satisfaction significant effect on consumer loyalty. Citra significant effect on consumer loyalty. F test can be concluded jointly variable product quality, price, location, satisfaction and image effect on consumer loyalty in Waroeng Special Sambal Sragen Branch. Results of a total of 0.869 R2 can be interpreted consumer loyalty in Waroeng Special Sambal Sragen Branch explained by the variable quality of the product, price, location and Satisfaction of 86.9%. Results of path analysis showed that: The use of intervening variables dauntuk satisfaction to loyalty product quality is effective and ineffective image. The use of intervening variables satisfaction and image for the price on loyalty is not effective. The use of intervening satisfaction and the image of the location for the variable is effective.Keywords: Product Quality, Price, Location, satisfaction, image, Consumer Loyalty